Repeated GnRH agonist doses for luteal support: a proof of concept. Issue 5 (November 2019) - Wiser, Amir; Klement, Anat Hershko; Shavit, Tal; Berkovitz, Arie; Koren, Roni Rahav; Gonen, Ofer; Amichay, Keren; Shulman, Adrian
Abstract: Research question: What are the safety and feasibility of repeated subcutaneous doses of gonadotrophin-releasing hormone (GnRH) agonist for luteal support in IVF cycles triggered by a GnRH agonist? Design: In this prospective trial, patients exhibiting oestradiol concentrations of over 2500 pg/ml after use of a GnRH agonist for triggering ovulation were initially randomized to GnRH agonist luteal support (0.1 mg subcutaneously every other day, starting on day 3 after embryo transfer) or to a control group supported by 80 µg of recombinant human chorionic gonadotrophin (HCG) on day 3 after embryo transfer. All patients underwent a day 5 blastocyst transfer. Randomization to the HCG luteal support was stopped owing to two cases of ovarian hyperstimulation syndrome (OHSS) and the study was continued solely with GnRH agonist luteal support. Results: The study included 39 women in the repeated GnRH agonist luteal support group and seven in the HCG micro dose group. There were no cases of OHSS among patients supported by a GnRH agonist, and no other adverse events were recorded. There were no cases of bleeding before the pregnancy test, and hence no cases of an insufficient luteal phase. A clinical pregnancy rate of 43.6% was achieved with GnRH agonist luteal support. Hormone dynamics during the stimulation cycle reflected rising LH and progesterone concentrations after the introduction of GnRH agonist support. Conclusions: Repeated doses of GnRH agonist every other day as a method of luteal support provided safe and effective luteal support for women who underwent GnRH agonist triggering in a GnRH antagonist IVF cycle.